Prescription patterns of antibiotics and analgesics in postoperative care at government cancer hospital: a prospective observational study - Pal, Avinash D.; Baig, Mirza S.; Gaikwad, Arvind (International Journal of Research in Medical Sciences, 2025)
Background: The prescription patterns of antibiotics and analgesics in postoperative care are critical for optimal recovery. This study aims to analyse the utilization of these medications in postoperative cancer patients at a government cancer hospital. Methods: A prospective, cross-sectional observational study was conducted at the government cancer hospital, Aurangabad, from March 2023 to August 2024. Prescription data were collected from 321 postoperative cancer patients, focusing on demographic details, drug classes, monotherapy versus combination therapy, and adherence to WHO prescribing indicators. Results: A total of 321 patients were included, resulting in a male-to-female ratio of 1.23. Antibiotics were prescribed 612 times, with inj. Metro being the most frequently used (33.01%), followed by inj. Augmentin (26.80%). Analgesics totalled 600 prescriptions, led by inj. PCM at 42.17% and inj. tramadol at 31.33%. Monotherapy accounted for 33.96% of antibiotic prescriptions and 16.82% of analgesics, while combination therapy was more common (41.43% for antibiotics and 83.18% for analgesics). Opioid analgesics comprised 58.33% of analgesic prescriptions, highlighting their role in postoperative pain management. Brand drugs were predominantly prescribed, 76.24% of the total. The average number of drugs per prescription was 3.78, and nearly all prescribed drugs (98.84%) were from the NLEM of India. Conclusions: The prescribing patterns adhered to WHO-DUS parameters, highlighting a strong preference for generic medications. Nitroimidazole and non-opioid analgesics were the most frequently prescribed drug classes, indicating a structured approach to postoperative care in cancer patients.